Kegiatan Mengajar Anak-anak Membaca Al-Qur'an Untuk Membantu Ustadz di Mushola Al-Muslimin Desa Kecomberan Kecamatan Talun Kabupaten Cirebon - Panji Thoriq Hilabi; Fadhli Taupiqurahman; Sifa Latifah (Darma Abdi Karya, 2023)
It is generally recognized that mosques or mushollas have a significant role for Muslims as the main place to carry out worship, including prayers, Quranic activities and others. The construction of a mosque and prayer room is one of the gifts from God, because the mosque is God's house on earth. The mosque means the center of all policies to Allah SWT, therefore we as Muslims have become the obligation of Muslims to study the Qur'an to practice it in everyday life. The LP3I Cirebon Polytechnic Thematic KKN group of Kecomberan Talun Village, Cirebon Regency took the initiative to help teach reading the Qur'an in one of the prayer rooms in Kecomberan Talun Village, Cirebon Regency. With this activity, it is hoped that it can increase interest for children to learn to read the Qur'an. The method used is by dividing the group to teach children between those who are still at the stage of reading iqro and those who can already read the Qur'an. With the holding of this activity, the mushola management felt helped because the teaching process became faster. Likewise, the children in the mushola have more time to do their schoolwork.